Sleep quality and well-being in junior elite athletes - Zepp, C.; Ohlert, J.; Kleinert, J. (Zeitschrift für Sportpsychologie, 2022)
Little cross-sectional and even less longitudinal research has been conducted on sleep quality and well-being in junior elite athletes. This study analyzed the relationship between subjective sleep quality and both psychological and physiological well-being in junior elite athletes using both a cross-sectional (N = 625 athletes; 49.9 % = female; M = 16.4 years, SD = 3.5 years) and a longitudinal approach (n = 79; 44.3 % = female; M = 16.4 years, SD = 3.5 years) over a period of M = 1.66 years (SD = 0.87 years). The results demonstrated that both samples showed that subjective sleep quality is correlated with well-being in junior elite athletes. In addition, the results showed that athletes of prepuberty age reported significantly better sleep quality than athletes during and after puberty, and that the relationship between sleep quality and psychological well-being is stronger in female junior athletes than in male athletes. This study emphasizes the need to ensure quality sleep in junior elite athletes.